Effects of different egg turning frequencies on incubation efficiency parameters - da S. Oliveira, Gabriel (Poult Sci, 2020)
This study aimed to evaluate the effects of different egg turning frequencies on incubation efficiency parameters. Nine hundred sixty brown fertile eggs, with an average weight of 52.20 ± 0.85 g, from 38-week-old CJD (Carijó Pesadão) breeder hens were randomly distributed among 4 treatments before incubation. Each treatment corresponded to a turning frequency, being 24 (control), 12, 6, or 3 times per day, at an angle of 45°, until day 18 of incubation. The experimental design was a randomized complete block design with 4 treatments. Analysis of the incubation parameters was based on 6 replications per treatment. The eggs that were turned 12, 6, and 3 times per day exhibited a decrease in hatchability of the fertile eggs of 6.61, 15.51, and 19.70%, respectively, when compared with the control group (91.84 ± 2.73%). With a decrease in turning frequency, there was a gradual increase in early (2.84 ± 1.89 to 14.31 ± 1.82%) and late (3.57 ± 1.39 to 8.05 ± 1.24%) mortality rates. An egg turning frequency of 24 times per day during incubation provided high hatchability rates. In contrast, the turning frequencies of 12, 6, and 3 times per day showed significant losses in hatchability.